2012
DOI: 10.1177/1934578x1200700603
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Taxane ABC Tricyclic Skeleton from Lycoctonine

Abstract: A new conversional synthesis of the ABC ring system of taxoids from the C 19-diterpenoid alkaloid lycoctonine was developed in 6 steps with 2% overall yield. The distinctive features of the conversion include pinacol rearrangement, enlargement of ring B, and opening of a four-membered ring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…We started to develop conversional synthesis of taxoids starting from C 19 -diterpenoid alkaloids since early 1990s. During the course, several novel approaches to the taxane ABC ring system and numerous intriguing reactions of C 19 -diterpenoid alkaloids have been reported [5][6][7][8][9][10][11][12][13]. We have found that modifications of ring B, including cleavage of C7-C17, enlargement of ring B, functionalization of C-7 and C-8 for assembly of the Δ 8,15 bridgehead double bond, and introduction of functional groups with specific configurations, were part of the critical steps to our successful conversions from aconitine-type C 19 -diterpenoid alkaloids [5][6][7] to the core structure of taxoids.…”
mentioning
confidence: 99%
“…We started to develop conversional synthesis of taxoids starting from C 19 -diterpenoid alkaloids since early 1990s. During the course, several novel approaches to the taxane ABC ring system and numerous intriguing reactions of C 19 -diterpenoid alkaloids have been reported [5][6][7][8][9][10][11][12][13]. We have found that modifications of ring B, including cleavage of C7-C17, enlargement of ring B, functionalization of C-7 and C-8 for assembly of the Δ 8,15 bridgehead double bond, and introduction of functional groups with specific configurations, were part of the critical steps to our successful conversions from aconitine-type C 19 -diterpenoid alkaloids [5][6][7] to the core structure of taxoids.…”
mentioning
confidence: 99%